PCMC-Based Feed-Forward Method for Alleviating Light-Load Current Distortion in a Boost PFC Converter - So, Jihun; Kim, Juil; Choi, Yeong-Jun (IEEE open journal of the Industrial Electronics Society, 2025)
This article proposes a predictive current mode control (PCMC)-based feed-forward method to mitigate light-load current distortion in boost power factor correction (PFC) converters. Since the PCMC generates the current reference for the next switching period and determines the duty cycle based on the voltage-second balance of the inductor, it is constrained by the on / off current ripple. This characteristic is more apparent under light load conditions, causing current distortion and degrading the total harmonic distortion (THD). This means that hardware modifications such as inductance and switching frequency are necessary to reduce current distortion. However, these hardware parameters are subject to physical limitations, such as size and price, and cannot be changed once they are set. The control loop of the boost PFC converter using PCMC consists of a voltage controller, which maintains a constant output voltage, and a PCMC, which regulates the input current. The output signals of the voltage controller and current shaping component are multiplied and sent to the PCMC as a reference. The proposed method modifies the current reference by adding a feed-forward term to the control loop to generate a new duty cycle. The feed-forward gain is designed based on the current ripple component and the duty cycle is updated every switching period. As a result, the input current distortion is mitigated by the modified duty cycle and the THD is reduced. The validity of the proposed method is experimentally verified using an Imperix B-box and a half bridge converter module.